Bojong Renged Village Government Development Communication Strategy in Empowering Entrepreneurship through Thematic Village Program - Ikhfi Imaniah; Eko Purwanto; Mirza Shahreza (Jurnal Mamangan, 2023)
The empowerment of entrepreneurship is of paramount importance in Indonesia, especially in rural areas, as an effort to enhance the well-being of the community. The thematic village program is considered one of the effective methods to facilitate entrepreneurship empowerment in rural areas. However, the success of this program greatly depends on the right communication strategies to promote and raise awareness about entrepreneurship within the community. This research aims to identify the types of effective communication strategies in building awareness and promoting the thematic village program for entrepreneurship empowerment in Bojong Renget Village. The theoretical framework used is Dell Hymes' SPEAKING framework, which will analyze the research subject from aspects such as Setting, Participants, Ends, Acts, Key, Instrumentalities, Norms, and Genre. This research employs a qualitative method with a descriptive approach. The result of this research is that the Bojong Renget Village Government is striving to enhance the economic potential and self-reliance of the community by prioritizing entrepreneurship. They involve individuals who are unemployed in the Thematic Village Program. Nevertheless, communication barriers between the village government and the village community remain a challenge in implementing entrepreneurship empowerment and the Thematic Village Program. The novelty of this research lies in its specific focus on communication strategies in entrepreneurship empowerment through the thematic village program in Bojong Renget Village.